THE EFFECT OF HOME STUDY INTENSITY AND LEARNING MOTIVATION ON MATHEMATICS LEARNING OUTCOMES OF GRADE VI STUDENTS AT STATE ELEMENTARY SCHOOL 2 MEREMBU - Aspari Aspari; Darmiany Darmiany; Ida Ermiana (PGMI Fakultas Tarbiyah Universitas Islam Jember, 2026)
The success of mathematics learning is not only influenced by the quality of classroom learning, but also by factors outside the classroom, such as the intensity of home learning and student learning motivation. However, most sixth-grade students at SD Negeri 2 Merembu showed low home learning intensity and lack of motivation to learn mathematics. This study aims to determine the effect of home learning intensity and learning motivation on the mathematics learning outcomes of sixth-grade students at SD Negeri 2 Merembu. This study used a quantitative approach with descriptive statistical research. Data analysis was conducted using multiple linear regression with the help of SPSS 26.0. The data used were from questionnaire results and student mathematics test scores. The results showed that home learning intensity and learning motivation did not significantly influence students' mathematics learning outcomes. This is indicated by a probability value of 0.172 > 0.05. This finding indicates that these two variables have not made a significant contribution to mathematics learning outcomes. This condition is thought to be influenced by other factors, namely teacher learning methods, students' basic mathematical abilities, a less conducive home learning environment, and limited guidance from parents. Therefore, schools and teachers need to implement more innovative learning strategies and increase cooperation with parents.